Associations for Citizen Science: Regional Knowledge, Global Collaboration. (11th November 2016) - Storksdieck, Martin; Shirk, Jennifer Lynn; Cappadonna, Jessica L.; Domroese, Meg; Göbel, Claudia; Haklay, Muki; Miller-Rushing, Abraham J.; Roetman, Philip; Sbrocchi, Carla; Vohland, Katrin
Since 2012, three organizations advancing the work of citizen science practitioners have arisen in different regions: The primarily US-based but globally open Citizen Science Association (CSA), the European Citizen Science Association (ECSA), and the Australian Citizen Science Association (ACSA). These associations are moving rapidly to establish themselves and to develop inter-association collaborations. We consider the factors driving this emergence and the significance of this trend for citizen science as a field of practice, as an area of scholarship, and for the culture of scientific research itself.